MELATI (Melek TI): Pelatihan Microsoft Office untuk Meningkatkan Keterampilan Digital Guru di SD-SMP Satu Atap 4 Gunungsari - Hasanah, Wirda; Sari, Elpa Nispita; Rahmayanti, Arini Fatma; Sari, Ida Ayu Nindya; Putri, Irma Husnantia; Gunada, I Wayan; Permata Anggarbini Rayes, Widuri (Rengganis Jurnal Pengabdian Masyarakat, 2024)
The Kampus Mengajar program, a key component of the Merdeka Belajar Kampus Merdeka initiative, aims to develop students' character and skills across various fields. This study focuses on assessing the impact of student participation in assisting teachers at SD-SMP Negeri Satu Atap 4 Gunungsari with technology adaptation, especially during the pandemic. The methodology employed is training, emphasizing technological adaptation. Observations and interviews revealed that students significantly aid in enhancing technology usage and understanding among teachers, positively impacting school learning and administration. This research highlights that student involvement helps overcome technology-related challenges faced by teachers, offering practical solutions and new experiences for both parties